Hairy roots of Hypericum perforatum L.: a promising system for xanthone production - Tusevski, Oliver; Stanoeva, Jasmina; Stefova, Marina; Kungulovski, Dzoko; Pancevska, Natalija; Sekulovski, Nikola; Panov, Saso; Simic, Sonja (Walter de Gruyter GmbH, 2013)
AbstractHypericum perforatum L. is a common perennial plant with a reputed medicinal value. Investigations have been made to develop an efficient protocol for the identification and quantification of secondary metabolites in hairy roots (HR) of Hypericum perforatum L. HR were induced from root segments of in vitro grown seedlings from H. perforatum, after co-cultivation with Agrobacterium rhizogenes A4. Transgenic status of HR was confirmed by PCR analysis using rolB specific primers. HR had an altered phenolic profile with respect to phenolic acids, flavonol glycosides, flavan-3-ols, flavonoid aglycones and xanthones comparing to control roots. Phenolics in control and HR cultures were observed to be qualitatively and quantitatively distinct. Quinic acid was the only detectable phenolic acid in HR. Transgenic roots are capable of producing flavonol glycosides such as quercetin 6-C-glucoside, quercetin 3-O-rutinoside (rutin) and isorhamnetin O-hexoside. The HPLC analysis of flavonoid aglycones in HR resulted in the identification of kaempferol. Transformed roots yielded higher levels of catechin and epicatechin than untransformed roots. Among the twenty-eight detected xanthones, four of them were identified as 1,3,5,6-tetrahydroxyxanthone, 1,3,6,7-tetrahydroxyxanthone, γ-mangostin and garcinone C were de novo synthesized in HR. Altogether, these results indicated that H. perforatum HR represent a promising experimental system for enhanced production of xanthones.